Explicit solutions of the Yang–Baxter-like matrix equation for an idempotent matrix. (January 2017) - Mansour, Saeed Ibrahim Adam; Ding, Jiu; Huang, Qianglian
Abstract: Let A be an idempotent matrix. We obtain an explicit expression for all the solutions of the quadratic matrix equation A X A = X A X, completing the task of finding general solutions of the equation explicitly with a given idempotent matrix A .